Cytotoxic effects of new-generation bulk-fill composites on human dental pulp stem cells - Kamalak, Hakan; Kamalak, Aliye; Taghizadehghalehjoughi, Ali (Cellular and Molecular Biology, 2018)
This study was performed to evaluate possible DNA damage in cells of human origin exposed to dental composites in vitro using a cytotoxic assay. Five bulk-fill composites were filled in molds and irradiated for 20 s. DPSCs were inoculated into 24-well plates. After the insert membrane was inserted and composites were added and the experiment was continued for 24/72 hours. In order to investigate the effects of the materials on DPSCs; its effect on apoptosis-regulating Bcl-2 gene, Human Beta-Defensins (HBDs 1-2) gene, Interleukin 6, 8, 10 expression level was examined. Also in order to check the cellular viability and stress factors; MTT assay, Total Antioxidant and Oxidant Status kits were used. At both irradiation times, all composites significantly affected analyses parameters used in primary DNA damage assessment or induced significant formation of cellular death. Cytotoxicity was detected in TE<SS<FBF<XB<VBF groups at 24 hour, and after 72 hour this sequence has changed.